Epidemiological and Histopathological Study of Appendicitis in Karbala Province (Indian Journal of Forensic Medicine & Toxicology, 2020)
The current study included an epidemiological prevalence study of appendicitis in Karbala province, where complete data were collected for the year 2018 from Al Hussein medical Hospital. The results showed that the total number of appendicitis in Karbala province was (636 ) cases , divided in to (299) and (286) for male and female respectively, while the secondary removal cases was (69). The percentage of infection was 47.012%, 42.12% and 10.85% for male , female and secondary removal. The statistical analysis showed that there were significant differences under (P> 0.05) between percentage of infection in male and female (0.01). Also this study included histopathological examination of appendectomy specimen. After surgical removal of appendix, the specimen directly fixed with 10% formalin and then do tissue processing. The microscopic examination showed obstruction of the lumen and infiltration of inflammatory cell within lumina properia, muscularis and adventatia.the mucosal epithelial was destruction with ulceration, also there are extensive lymphoid hyperplasia.